Management of pemphigus vulgaris: case report - Rahmaningsih, Widi; Santosa, Agus (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Background: Pemphigus Vulgaris is an autoimmune disease attacking the skin and mucous membranes. This disease is considered a rare disease. Epidemiological data for Pemphigus Vulgaris in Indonesia remains limited, correspondingly, nursing management in this disease. This study aims to describe nursing management in patients with Pemphigus Vulgaris. Case presentation: a case of Pemphigus Vulgaris in a 28-year-old male was reported, with complaints of blisters all over his body appearing since 2019 and have not been completely recovered at the Banyumas General Hospital, Central Java, Indonesia. Conclusion: A combination of wound care, nutrition, vitamins, and pharmacology can accelerate the recovery of patients with Pemphigus Vulgaris